MON-264 Pleotropic Clinical Presentation in Two Brazilians Patients with Confirmed IgG4-Related Hypophysitis - de Oliveira, Rafael (J Endocr Soc, 2020)
Background: Hypophysitis is a rare condition characterized by inflammation of the pituitary gland, usually resulting in hypopituitarism and pituitary enlargement with mass effect symptoms. IgG4-related hypophysitis can occur alone or as part of a multiorgan disease. Treatment with glucocorticoids is effective in 97% of the cases in reducing pituitary mass. Clinical cases: Case #1. A 56-yrs man with previous diagnosis of Mikulicz syndrome was referred to our service with fatigue and erectile dysfunction. Laboratory evaluation revealed hypogonadotropic hypogonadism, hyperprolactinemia (PRL=108 ng/mL) and central hypothyroidism. Sellar MRI depicted a pituitary mass with pituitary stalk thickening and a homogeneous uptake of gadolinium. During clinical follow-up, he also presented retroperitoneal fibrosis and IgG4-related disease was confirmed by serum IgG4 elevation and a pathological review of the previous salivary gland biopsy.Prednisone 80 mg/d treatment was initiated, with recovery of the thyrotrophic axis, reduction of PRL levels and significant reduction of the pituitary lesion. Due to maintenance of inflammatory activity and worsening of renal function, azathioprine therapy was associated, with subsequent inclusion of rituximab. Case #2. A 16-yrs boy was referred to our service presenting severe headache, bilateral visual deficit, right eyelid ptosis, hyposmia, polyuria and polydipsia. Cranial MRI depicted an extensive skull base mass involving pituitary gland, optic nerves, cavernous sinuses, olfactory bulb and clivus). Hormonal evaluation confirmed normoprolactinemia, hypogonadotropic hypogonadism and diabetes insipidus. Biopsy of the lesion revealed meningeal inflammation with immunohistochemistry suggesting IgG4-related sclerosing disease. No other organs were affected. An important lesion reduction and gonadotropic axis recovery occurred after 40 days of prednisone 60mg/d. After the drug withdrawal, methotrexate was introduced. However, after three years, headache and hyposmia recurred. A new MRI revealed increase of lesion and mycophenolate and rituximab were initiated, with clinical improvement without recurrences over time. Conclusion: Although a rare disease, IgG4-related disease should be included in the differential diagnosis amongst pituitary masses, with or without other affected organs. Immunosuppression with corticosteroids is the first treatment choice and other alternatives must be used in case of persistence of disease activity or relapse. These are very few Brazilian patients reported with IgG4 related disease. We described two cases with IgG4-related hypophysitis: one young patient, without involvement of other organs and another of middle age with systemic involvement, reinforcing the pleotropic clinical picture. Both required rituximab therapy due to disease progression.